Anthelmintic Treatment of Sheep and the Role of Parasites Refugia in a Local Context - Johan Höglund; Katarina Gustafsson (Animals, 2023)
Gastrointestinal nematodes in grazing livestock are ubiquitous and can cause severe damage, leading to substantial losses in agricultural yields. It is undeniable that the integrated use of anthelmintics is often an essential component of successful intensive livestock management. However, anthelmintic resistance has been a major challenge for several decades, especially in pasture-based lamb production. Measures are therefore needed to reduce the risk and prevent further spread. In many countries with more extensive lamb production and pronounced resistance problems than in Sweden, the importance of keeping parasites in refugia is emphasised. To ensure that treatment is necessary, the Swedish model is based on deworming certain groups of ewes based on the parasitological results of a faecal examination and then releasing them with their lambs to safe pastures. This is intended to reduce the risk of infection, which ultimately reduces the number of subsequent treatments. Whether this preventive strategy in turn means an increased risk of resistance is debatable. In this review, we explain the importance of parasites in refugia and how they can help delay the development of resistance to anthelmintics. We also discuss how likely it is that our model contributes to an increase in resistance risk and whether there is reason to question whether it is a sustainable strategy in the long term.